2019
DOI: 10.1038/s42003-019-0645-6
|View full text |Cite
|
Sign up to set email alerts
|

A common mechanism allows selective targeting of GluN2B subunit-containing N-methyl-D-aspartate receptors

Abstract: N-methyl-D-aspartate receptors (NMDARs), especially GluN2B-containing NMDARs, are associated with neurodegenerative diseases like Parkinson, Alzheimer and Huntington based on their high Ca2+ conductivity. Overactivation leads to high intracellular Ca2+ concentrations and cell death rendering GluN2B-selective inhibitors as promising drug candidates. Ifenprodil represents the first highly potent prototypical, subtype-selective inhibitor of GluN2B-containing NMDARs. However, activity of ifenprodil on serotonergic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(58 citation statements)
references
References 50 publications
1
57
0
Order By: Relevance
“…The NR2B subunit is involved in neurodegenerative processes in patients with Parkinson’s and Huntington’s diseases as well as AD [ 33 ]. Therefore, efficient modulators of GluN2B-containing NMDARs are a promising tool for further investigation and potential treatment of these diseases [ 34 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The NR2B subunit is involved in neurodegenerative processes in patients with Parkinson’s and Huntington’s diseases as well as AD [ 33 ]. Therefore, efficient modulators of GluN2B-containing NMDARs are a promising tool for further investigation and potential treatment of these diseases [ 34 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…When upregulated, GluN2B can hinder the neuronal network remodeling response to plasticity [ 66 ]. Increases in GluN2B have also been shown to be related to neurodegenerative pathways in diseases such as Parkinson’s, Alzheimer’s, and Huntington’s disease [ 67 ]. Whether the increase in GluN2B after experimental TBI is related to the later development of post-TBI neurodegeneration is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…It is observed that continued NMDAR activation can lead to neuronal injury [20]. Unbalance of NMDARs is widely suggested to be associated with the occurrence and development of various central nervous system diseases, such as ischemic stroke, Alzheimer disease, Parkinson disease and so on [19,21]. NR2B is a subtype of NMDAR, which is associated with the over activation of NMDAR, followed by the neuronal damage [22].…”
Section: Discussionmentioning
confidence: 99%